Organization and expression of the Rhodobacter sphaeroides cycFG operon. - Flory, J E (1995)
The Rhodobacter sphaeroides cycFG operon has been cloned, sequenced, and mapped to approximately coordinate 2500 of chromosome I. The cycF gene encodes cytochrome c554, a member of the class II family of soluble cytochrome c proteins. The cycF open reading frame includes a 20-amino acid extension at its N terminus which has not been detected in cytochrome c554. Antiserum against cytochrome c554 shows that this protein is localized to the periplasm of wild-type cells, which suggests that this N-terminal extension functions as a signal peptide. The predicted cycG gene product is a diheme cytochrome c with a subunit molecular mass of approximately 32 kDa. While a cytochrome with the properties predicted for CycG has not been reported for R. sphaeroides, we have tentatively identified this protein as a heme-staining polypeptide that is associated with membranes. CycG could have an overall structure similar to that of several other electron carriers, since the similarity between the predicted amino acid sequence of CycG and other multiheme cytochrome c proteins extends throughout the polypeptide. The cycFG transcript is approximately 1,500 nucleotides long and has a single 5' end 26 nucleotides upstream of the start of cycF translation. Expression of cycFG is regulated at the level of mRNA accumulation, since approximately fivefold-higher levels of both cycF-specific transcript and cytochrome c554 protein are detected in cell extracts from aerobic cultures in comparison with those from anaerobically grown cells. Although cytochrome c554 was detected under all growth conditions tested, the highest levels of this protein were found when cells generate energy via aerobic respiration.